Reframing Professionalism: English Teachers’ Digital Competence and Identity in Modern Pesantren - Fadia Nasywa Umnia; Diska Fatima Virgiyanti; Faiz Rizki Muhammad (Nusantara: Jurnal Pendidikan Indonesia, 2026)
Purpose – This study examines how English teachers in modern pesantren redefine professionalism by integrating digital competence with Islamic educational values. While digital competence has been widely studied, its role in shaping teacher identity in faith-based contexts, particularly Indonesian pesantren remains underexplored. This study investigates how digital literacy is negotiated alongside moral and spiritual responsibilities. Methods – A qualitative design was employed using semi-structured interviews with 12 English teachers from five modern pesantren across Indonesia. Participants were purposively selected to ensure diversity in institutional context, gender, and teaching experience. Data was analysed thematically using Braun and Clarke’s (2019) six-phase framework to identify patterns related to digital integration and teacher identity. Findings – Digital competence is not treated as a neutral technical skill but is interpreted through the normative framework of pesantren education. This process constructs a hybrid form of professionalism in which pedagogical innovation is balanced with spiritual accountability. Technology adoption is therefore guided not only by efficiency or innovation but also by moral considerations such as appropriateness, discipline, and institutional values. As a result, teachers apply digital tools selectively, enhancing learning while restricting practices perceived to conflict with the pesantren’s ethical ethos. Research Implications – The study is limited by its small qualitative sample and focus on selected pesantren, which may constrain generalizability. However, it underscores the need to integrate digital competence with value-based professional development in Islamic educational contexts.